VRŠILSKOST V SLOVENŠČINI MED POMENOM IN IZRAZOM (Philological Studies, 2019)
The person as a grammatical category, expressing the relationship between participants and/or non-participants and an occurence/action/state, is distinguished from the subject as a nominative sentence element, both are basic structural (clause-forming) elements. Within the scope of indicative and suprasentential syntax, the communicative capabilities enable and determine the expression or non-expression of the subject. The expressed or unexpressed subject can be the formal subject (expressing a nonnominal person), the indefinite/generalized subject (expressing the indefinite/ generalized person), or the definite subject (expressing the definite /verbal/ person). The decrease of the concrete referential agent leads to the use of the first-person plural and the second-person plural or singular, e.g., Govorimo 'We talk', Govorite/ Govoriš 'You talk/You talk', Rečete/Rečeš 'You say/You say', etc., and then to use of the third-person plural and singular with the pronominal variants ljudje 'people' and človek 'man', as well as with the reflexive pronoun se, denoting general agentness, e.g., Opozarja se na marsikaj, človek pa navadno vidi samo sebe 'Many a thing is warned against, but man usually only sees himself'. In case the third person is in the neuter genter, this leads to indetermination, indefiniteness, and consequently generalization. Therefore, what remains in extreme cases of impersonal (subjectless) sentences related to weather, e.g., Lije 'It's pouring' or Rosi 'It's drizzling', is the definiteness of the form that expresses the given (weather-related) occurrence as as a synthesis of agentness and processuality. However, the generalization of the actor or the subject enables the translation of a concrete message into a (generalized) statement in all cases, e.g., Tone izpolnjuje svoj dolg > *Vsak človek izpolnjuje svoj dolg > Vsak (človek) mora izpolnjevati svoj dolg 'Tone is meeting his debt > *Everybody is meeting debt > Everyone must meet their debt'.
Keywords: person, subject, agentness, Slovene